BABEL3&3a : Crustal-Scale Structures of the Precambrian Svecofennian Accretionary Orogen in the Fennoscandian Shield - Korja, Annakaisa; Heikkinen, Pekka Juhani; Tiira, T.; Nikkilä, Kaisa Mirjami (2018)
Peer reviewed